2021
DOI: 10.3389/fpsyg.2021.600999
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Dissection of Neural Circuits Underlying Stress-Induced Mood Disorders

Abstract: Objectives: This review aims to (i) summarize the literature on optogenetic applications of different stress-induced mood disorder models of the medial prefrontal cortex (mPFC) and its projection circuits, and (ii) examine methodological variability across the literature and how such variations may influence the underlying circuits of stress-induced mood disorders.Methods: A variety of databases (PubMed, Web of Science, Elsevier, Springer, and Wiley) were systematically searched to identify optogenetic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The authors reported that only about 13% of the injured animals were found to be "vulnerable, " showing increased exploration of anxiogenic regions during testing compared to baseline behavior and to sham-treated animals (Popovitz et al, 2021). The behavior of the vulnerable mice had neurobiological correlates in the medial prefrontal cortex, basolateral amygdala, and ventral hippocampus; all areas that are associated with stress and anxiety (Almeida-Suhett et al, 2014;Bryant and Barker, 2020;Kenwood et al, 2021;Liu et al, 2021;McCorkle et al, 2021;Pentkowski et al, 2021). Statz et al employed a different "affective profiling" technique to identify "affected" and "unaffected" rats 3 weeks or 6 months following exposure to repeated blast overpressure (Statz et al, 2019).…”
Section: Use Of Multiple Tests and Alternative Data Analysis Methodsmentioning
confidence: 99%
“…The authors reported that only about 13% of the injured animals were found to be "vulnerable, " showing increased exploration of anxiogenic regions during testing compared to baseline behavior and to sham-treated animals (Popovitz et al, 2021). The behavior of the vulnerable mice had neurobiological correlates in the medial prefrontal cortex, basolateral amygdala, and ventral hippocampus; all areas that are associated with stress and anxiety (Almeida-Suhett et al, 2014;Bryant and Barker, 2020;Kenwood et al, 2021;Liu et al, 2021;McCorkle et al, 2021;Pentkowski et al, 2021). Statz et al employed a different "affective profiling" technique to identify "affected" and "unaffected" rats 3 weeks or 6 months following exposure to repeated blast overpressure (Statz et al, 2019).…”
Section: Use Of Multiple Tests and Alternative Data Analysis Methodsmentioning
confidence: 99%
“…Previous reviews have drawn conclusions that connect optogenetic interventions to the disease mechanisms of depression. 27 , 28 , 30 , 82 , 83 , 84 Most of these reviews provide qualitative analyses of a wide range of research results and discuss relevant brain targets involved in the mechanistic picture of depression. In addition, some articles discussed the accessibility of specific neuronal circuits for DBS.…”
Section: Discussionmentioning
confidence: 99%